2017
DOI: 10.4236/jmf.2017.72023
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Bank Ownership Structure and Risk Preference

Abstract: Company's risk-taking behavior has a significant impact on corporate earnings' growth and the social economic development, and different ownership structure will affect the company's risk preference. In this paper, with the 25 Chinese listed banks, the empirical tests the effect of ownership structure on bank's risk preference. The result showed that the correlation between ownership concentration and the bank's risk preference is positive; the bank's risk preference and shareholding separation have inverted u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Tuy nhiên đa số các nghiên cứu đều tập trung vào mối quan hệ giữa cấu trúc sở hữu và hiệu quả hoạt động, khá ít nghiên cứu về mối quan hệ giữa cơ cấu sở hữu và rủi ro của ngân hàng 6 . Tương tự tại VN, qua tìm hiểu của tác giả, cũng có rất ít các nghiên cứu thực nghiệm về chủ đề này cho ngành ngân hàng, đặc biệt trong bối cảnh ngành ngân hàng đang có nhiều thay đổi mạnh mẽ theo định hướng hội nhập quốc tế của chính phủ.…”
Section: Giới Thiệuunclassified
“…Tuy nhiên đa số các nghiên cứu đều tập trung vào mối quan hệ giữa cấu trúc sở hữu và hiệu quả hoạt động, khá ít nghiên cứu về mối quan hệ giữa cơ cấu sở hữu và rủi ro của ngân hàng 6 . Tương tự tại VN, qua tìm hiểu của tác giả, cũng có rất ít các nghiên cứu thực nghiệm về chủ đề này cho ngành ngân hàng, đặc biệt trong bối cảnh ngành ngân hàng đang có nhiều thay đổi mạnh mẽ theo định hướng hội nhập quốc tế của chính phủ.…”
Section: Giới Thiệuunclassified
“…Whereas, Srivastav and Hagendorff (2016), found that there is the risk-averse behavior of insider ownership has been observed and also pursuing the strategies of risk reduction. Similarly, Zhong (2017), analyzed the Chinese banking system and found that lack of agency issues reduces the chances of failure in private ownership structure of the banks. Moreover, Dong, Girardone, and Kuo (2017), conducted the study on Chinese banks and examined that bank risk-taking increases when up to 5 percent shares held by insiders and decreases bank risk-taking when up to 25 percent or more shares held by insiders.…”
Section: Private Ownership Structure and Bank Risk Takingmentioning
confidence: 99%